Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention Karyawan Bagian Medis RS â€œXâ€ Pekanbaru - Sandora, Meri; Andrala, Athaariqi (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
This research was conducted at â€œXâ€ Hospital Pekanbaru. The purpose of this study was to determine the effect of job satisfaction and organizational commitment on employee turnover intention of the medical department of â€œXâ€ Hospital Pekanbaru, either partially or simultaneously. The population in this study were employees of the medical section of â€œXâ€ Hospital Pekanbaru as many as 108 employees and the sample used in this study amounted to 85 people. The method of determining the sample in this study used the method of proportionate stratified random sampling. The data used are primary data and secondary data. The data analysis method used is descriptive analysis method and quantitative analysis method. The results showed that job satisfaction partially affected the employee turnover intention of the medical department of â€œXâ€ Hospital Pekanbaru. Organizational commitment partially affects the turnover intention of employees in the medical department of â€œXâ€ Hospital Pekanbaru. Simultaneously, job satisfaction and organizational commitment have an influence on employee turnover intention in the medical department of â€œXâ€ Hospital Pekanbaru, while the magnitude of the effect is 67.7%, while the rest (32.3%) is influenced by other variables not examined in this study